2002
DOI: 10.2337/diacare.25.11.1952
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Planned Care and a Diabetes Electronic Management System on Community-Based Diabetes Care

Abstract: OBJECTIVE -The Mayo Health System Diabetes Translation Project sought to assess models of community-based diabetes care and use of a diabetes electronic management system (DEMS). Planned care is a redesigned model of chronic disease care that involves guideline implementation, support of self-management, and use of clinical information systems.RESEARCH DESIGN AND METHODS -We studied adult diabetic patients attending three primary care practice sites in Wisconsin and Minnesota. We implemented planned care at al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 15 publications
4
98
0
Order By: Relevance
“…Hand searches did not yield additional studies. Forty-eight eligible studies with seven companion papers [65][66][67][68][69][70][71] were identified, including 12 RCTs, 18,21,30,32,35,39,40,44,[52][53][54]56 four nonrandomized studies, 23,29,31,38 and 32 pre-post studies. 17,19,20,22,24 -28,33,34,36,37,41-43,45-51,55,57-64 The 48 studies had a total of 162,157 participants (range, 30 to 27,270) and follow-up periods ranging from 4 months to 4 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hand searches did not yield additional studies. Forty-eight eligible studies with seven companion papers [65][66][67][68][69][70][71] were identified, including 12 RCTs, 18,21,30,32,35,39,40,44,[52][53][54]56 four nonrandomized studies, 23,29,31,38 and 32 pre-post studies. 17,19,20,22,24 -28,33,34,36,37,41-43,45-51,55,57-64 The 48 studies had a total of 162,157 participants (range, 30 to 27,270) and follow-up periods ranging from 4 months to 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…18,21 Mean duration of diabetes was 9.4 years (SDϭ7.9) (20 studies). Nineteen studies provided information regarding diabetes treatment, [17][18][19]21,28,29,31,38,39,41,43,44,48,49,54,59,60,63,64 and insulin was the treatment most often used. 18,19,21,28,29,31,38,41,43,44,48,49,54,60,63,64 The quality of the studies varied; in particular, randomization procedure and allocation concealment among RCTs were rarely reported, and a funnel plot suggested the possibility of publication bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is substantial evidence to support this third point as well. [32][33][34][35][36][37][38] While the clinical points made by Phillips disease care. In chronic disease management, the task faced by health care providers (and the patient) is one in which decisions are made to control a process that is manifest in varying states of patient health.…”
Section: Physician Factors That Contribute To Clinical Inertiamentioning
confidence: 99%